2006
DOI: 10.1007/s11250-006-4308-5
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis for community participation in trypanosomosis control in The Gambia

Abstract: The shift towards community participation in the eradication of trypanosomosis calls for investigation the underlying incentive structure for individuals in the community to cooperate in the provision of various control methods. Survey data were used to assess patterns of the community's demand for insecticide pour-ons and trypanocidal drugs and factors affecting individual demand in The Gambia. The results show that insecticide pour-on is strongly preferred. Similarly, farmers revealed a preference for commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A sense of group cohesion [39] and enthusiasm were identified as additional important elements. Furthermore a study on community participation in efforts against animal trypanosomiasis in Gambia suggested that farmers are more community-oriented than individualistic, when expressing preferences for disease control scheme [40]. A community-centred and culturally sensitive approach in tsetse control has been shown to contribute significantly to the reduction of tsetse flies and incidence of HAT in previous research [19]–[21], [24], [41], [42] and our findings underline the importance of understanding anthropological factors if the full benefits of vector control are to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…A sense of group cohesion [39] and enthusiasm were identified as additional important elements. Furthermore a study on community participation in efforts against animal trypanosomiasis in Gambia suggested that farmers are more community-oriented than individualistic, when expressing preferences for disease control scheme [40]. A community-centred and culturally sensitive approach in tsetse control has been shown to contribute significantly to the reduction of tsetse flies and incidence of HAT in previous research [19]–[21], [24], [41], [42] and our findings underline the importance of understanding anthropological factors if the full benefits of vector control are to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…These studies describe the uses and misuses of drugs by farmers and animal health workers as a consequence of their knowledge and perceptions of diseases and drugs. They provide information on farmers' perceptions and self-assessment of veterinary drug-dispensing services [see for example Somda et al ( 34 ) for Gambia; Enahoro et al ( 33 ) for Ghana and Tanzania; Machila et al ( 35 , 37 ) and Higham et al ( 36 ) for Kenya; Moffo et al ( 8 ) for Cameroon; Soudre et al ( 38 ) for Burkina Faso]. Many of these studies highlight farmers' lack of knowledge, awareness, or compliance ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%